Efeito da deficiência da testosterona nas subpopulações mitocondriais em cardiomiócitos de ratos - Lima, Patrícia Ribeiro do Val (2017)
Testosterone deficiency (hypogonadism) is one of the risk factors for cardiovascular disease. When it occurs, it causes reduction in myocardial contractility. Considering that there is a close correlation between oxidative metabolism and myocardial contractility, the present study aimed to obtain new information about the effects of testosterone deficiency on two spatially distinct cardiac mitochondrial subpopulations: subsarcolemmal mitochondria (SSM) and interfibrillar mitochondria (IFM). Male Wistar rats (n = 30), of the albino line Rattus norvegicus, were used to evaluate the function and structure of these cardiac mitochondrial subpopulations with and without testosterone deficiency. The sample was randomly divided into three groups: 1) SHAM group (control); 2) OQT group (orchidectomized) and 3) OQT + T group (orchidectomized with testosterone replacement). The results showed four main findings, as follows: a) the total mitochondrial yield in the subsarcolemmal subpopulation (SSM) of the orchidectomized group (OQT) showed a higher amount of mitochondrial protein in relation to the SHAM and OQT + T groups, however there was no difference in interfibrillar fraction (IFM); b) membrane potential, internal size and complexity in the interfibrillar subpopulation (IFM) from the OQT group were higher compared to the SHAM and OQT + T groups, but there was no difference in the subsarcolemmal subpopulation (SSM); c) the rate of oxidative phosphorylation with the substrates glutamate + malate, pyruvate + malate, palmitoyl-L-carnitine and rotenone + succinate in the interfibrillar subpopulation (IFM) of the OQT group was lower in comparison with the SHAM and OQT + T groups, and testosterone replacement (OQT + T) was able to restore these alterations; there was decrease in oxidative phosphorylation in the SSM group, with palmitoyl-L-carnitine as substrate; d) mitochondrial swelling showed no difference in calcium retention capacity in all groups in both subpopulations (IFM and SSM); in addition, testosterone deficiency affected mitochondrial calcium uptake (calcium green 5N assay), demonstrating that the IFM subpopulation from the OQT group had a higher calcium retention capacity. In summary, in the cardiac interfibrillar mitochondrial subpopulation, changes in oxidative phosphorylation, morphology and calcium retention capacity occurred in rats with testosterone deficiency. Testosterone replacement was able to restore all changes induced by orchiectomy. Therefore, the present study showed specific differences in subsarcolemmal and cardiac interfibrillar mitochondrial subpopulations as a result of testosterone deficiency.